Manajemen dan Pengembangan Zoom Meeting - Winda Kustiawan; Lola Fahira Mutahar; Rayan Al-Ghazali (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Visual media are modern learning media that can be used to hear and see images. Visual media can be used to increase student interest in learning. Online learning using visual-based applications is very effective. The Zoom Meeting application is a video-based application that is used as an online learning media. This application is the same as the meet application, whatsapp video and others. The difference lies in the features used. Not only used for online learning, this application is also used for office or other matters. The Zoom Meeting application developed rapidly during the emergence of the Covid-19 outbreak. The features contained in Zoom Meeting help the process of communicating between students and teachers. Since the Covid-29 pandemic, Zoom Meeting has provided many benefits for its users.